KEBIJAKAN PEMERINTAH DESA TELUK JIRA DALAM RANGKA MENINGKATKAN PRODUKSI PERTANIAN KELAPA PASCA COVID 19 - Triyana Syahfitri; Rapika Ristama; Nuraini; Muhammad Irfan; Zainal Mutakin (JURNAL RISET INDRAGIRI, 2023)
Government policy in making efforts to empower coconut farmers must still be a major concern, because most of the people's livelihoods in Teluk Jira Village are coconut farmers. The government must provide an empowerment program that benefits coconut farmers. Because without a clear program, until now the coconut processing carried out by the community is still the same as before, namely processed into smoked copra with an unstable selling price so that people's income is still low. Therefore the role of the government is urgently needed in making efforts to empower coconut farmers, such as financial assistance programs, socialization, as well as training and understanding of processed coconut products that can be sold at relatively balanced prices so as to be able to make the community independent in managing and developing agricultural businesses coconut, so that people's income increases and the fulfillment of all the necessities of life.